Metabolic dynamics in astrocytes and microglia during post-natal development and their implications for autism spectrum disorders - Cantando, Iva; Centofanti, Cristiana; D’Alessandro, Giuseppina; Limatola, Cristina; Bezzi, Paola (Frontiers in Cellular Neuroscience, 2024)
Autism Spectrum Disorder (ASD) is a complex neurodevelopmental condition characterized by elusive underlying mechanisms. Recent attention has focused on the involvement of astrocytes and microglia in ASD pathology. These glial cells play pivotal roles in maintaining neuronal homeostasis, including the regulation of metabolism. Emerging evidence suggests a potential association between ASD and inborn errors of metabolism. Therefore, gaining a comprehensive understanding of the functions of microglia and astrocytes in ASD is crucial for the development of effective therapeutic interventions. This review aims to provide a summary of the metabolism of astrocytes and microglia during post-natal development and the evidence of disrupted metabolic pathways in ASD, with particular emphasis on those potentially important for the regulation of neuronal postnatal maturation by astrocytes and microglia.